An Assessment of Systemic Factors and COVID-19 Mortality in Africa - Ayomide Owoyemi; Tolulope Balogun; Joy Okoro; Tariro Ndoro; Oluwakayode Fasominu; Adejare Atanda; Ibraheem Abioye (Frontiers Media S.A., 2022)
Objectives: The objective of this study was to examine the association between several country-level systemic indices and the deaths from COVID-19 across African countries.Method: Regression analyses were conducted to test the association between selected indices and deaths from COVID-19 across African countries. All tests were run at the α = 0.05 level of significance.Result: We found a statistically significant correlation between total COVID-19 deaths per million and Stringency Index (p-value <0.001) and Human Development Index (p-value <0.001). Multiple regression analysis showed that Stringency Index was the only variable that remained significant when other factors are controlled for in the model.Conclusion: Countries in Africa with poorer governance, inadequate pandemic preparedness and lower levels of development have unexpectedly fared better with respect to COVID-19 deaths mainly because of having a younger population than the countries with better indices.